2019
DOI: 10.1002/jsc.2300
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder salience and collaboration decisions in microfinance organizations: Evidence from developing Islamic country's context

Abstract: Studies mutually disagree on which stakeholders matter to the managers. Based on a finer differentiation of salience attributes—power, legitimacy, urgency, and proximity—this study finds that stakeholders that possess four attributes' types—that is, structural legitimacy, utilitarian power, organized proximity, and criticality—are considered salient by managers of microfinance organizations. Collaboration with salient stakeholders is considered indispensable by microfinance managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The conclusion is that clear and effective communication of Islamic values through marketing efforts, website content, and customer interactions is crucial in building a strong Islamic brand, as it aims to educate customers about the bank's ethos and foster their trust. Moreover, partnerships and collaborations with Islamic scholars and institutions can significantly bolster the credibility of an Islamic bank [63]. The bank can demonstrate its commitment to upholding Islamic principles by seeking guidance and endorsements from reputable religious authorities [64].…”
Section: Includedmentioning
confidence: 99%
“…The conclusion is that clear and effective communication of Islamic values through marketing efforts, website content, and customer interactions is crucial in building a strong Islamic brand, as it aims to educate customers about the bank's ethos and foster their trust. Moreover, partnerships and collaborations with Islamic scholars and institutions can significantly bolster the credibility of an Islamic bank [63]. The bank can demonstrate its commitment to upholding Islamic principles by seeking guidance and endorsements from reputable religious authorities [64].…”
Section: Includedmentioning
confidence: 99%
“…Their failure may bring stakeholders to withdraw subsidized support, and microfinance organizations may become increasingly commercial (Ashta, 2019). The most important stakeholders may depend upon whether they have structural legitimacy, utilitarian power, organized proximity, and criticality (Khurram, Khurram, & Memon, 2019). More specifically, we found that organizations are co‐creating microfinance strategies by partnering with technology providers and using crowdfunding, efficient information systems, mobile banking, and credit scoring (Ashta, 2012).…”
Section: Research Directionsmentioning
confidence: 99%
“…Microfinance institutions (MFIs) make a valuable contribution to improving financial inclusion by providing convenient and affordable credit, savings and other financial services, especially to poor households and micro enterprises (Ben Abdelkader & Mansouri, 2019; Bros et al, 2022; Das, 2018; Garcia et al, 2022; Garcia‐Rodriguez et al, 2019; Hermes & Hudon, 2018; Khurram et al, 2019; Milana & Ashta, 2020). MFIs can help low‐income households reduce credit constraints and borrowers' reliance on informal lenders (loan sharks) (Bros et al, 2022; Islam & Pakrashi, 2020; Singhe, 2020).…”
Section: Introductionmentioning
confidence: 99%